Self-regulated learning in higher education : strategies adopted by computer programming students - Pedrosa, Daniela (2016)
Trabalho apresentado em PAEE/ALE’2016, 8th International Symposium on Project Approaches in Engineering Education (PAEE) and 14th Active Learning in Engineering Education Workshop (ALE)